Beyond retribution : a New Testament vision for justice, crime, and punishment - Marshall, Christopher D (Grand Rapids, MI : William B. Eerdmans Pub., 2001)
Recently a growing number of Christians have actively promoted the concept of "restorative justice" and attempted to develop programs for dealing with crime based on restorative principles. But is this approach truly consistent with the teaching of Scripture? To date, very little has been done to test this claim. Beyond Retribution fills a gap by plumbing the New Testament on the topics of crime, justice, and punishment. Christopher Marshall first explores the problems involved in applying ethical teachings from the New Testament to mainstream society. He then surveys the extent to which the New Testament addresses criminal justice issues, looking in particular at the concept of the justice of God in the teachings of Paul and Jesus. He also examines the topic of punishment, reviewing the debate in social thinking over the ethics and purpose of punishment -- including capital punishment -- and he advocates a new concept of "restorative punishment." The result of this engaging work is a biblically based challenge to imitate the way of Christ in dealing with both victims and offenders. - Publisher
Introduction: gaining a perspective -- The arena of saving justice: the justice of God in Paul and Jesus -- Punishment that fits: the purpose and ethics of punishment -- Vengeance is mine: divine and human punishment in the New Testament -- Justice that kills: is there a place for capital punishment? -- Conclusion: forgiveness as the consummation of justice
Includes bibliographical references (p. 285-316) and indexes
Keywords: Criminal justice, Administration of; Christianity and justice